2013
DOI: 10.14260/jemds/1413
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fetal Vibroacoustic Stimulation Test as an Adjunct to Non-Reassuring Cardiotocography During Labour in Low-Resource Settings

Abstract: This randomized controlled trial (RCT) was undertaken to evaluate the effect of vibroacoustic stimulation (VAS) on the fetal heart rate tracing, mode of delivery and perinatal outcomes, when cardiotocographs (CTG) showed non-reassuring features during labour. In this RCT, 60 women beyond 30 weeks' gestation in labour having non reassuring CTG for 20 min were recruited in either study group (VAS group) or control group (non-VAS group). Women in the study group received VAS for 3 sec up to 3 occasions at an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Table 1 provides the characteristics of the included studies. Our review identified eight intervention studies, including randomized controlled trials (RCTs) 12,13,18–20,23 and quasi‐experimental studies 17,22 ; and 59 observational studies, including cohort studies, 15,24–26,28–30,32,34,36–38,40,41,43,46,47,50,56–58,61,63,65–71,73–75,77,78 case–control studies, 27,33,35,39,42,44,45,48,49,52,53,55,62,64,72 before and after studies, 14,16,21,31 and cross‐sectional studies 51,54,60,76,79 . These studies were published between 1974 and 2023.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 provides the characteristics of the included studies. Our review identified eight intervention studies, including randomized controlled trials (RCTs) 12,13,18–20,23 and quasi‐experimental studies 17,22 ; and 59 observational studies, including cohort studies, 15,24–26,28–30,32,34,36–38,40,41,43,46,47,50,56–58,61,63,65–71,73–75,77,78 case–control studies, 27,33,35,39,42,44,45,48,49,52,53,55,62,64,72 before and after studies, 14,16,21,31 and cross‐sectional studies 51,54,60,76,79 . These studies were published between 1974 and 2023.…”
Section: Resultsmentioning
confidence: 99%
“…These were published between 2013 and 2022, and the studies included three RCTs, a quasi‐experimental study, and one before and after study. In this study, monitoring techniques included vibroacoustic stimulation, 19 CTG with a computerized decision support system, 20 fetal scalp blood sampling, 22 education package of fetal heart rate monitoring, 21 and fetal acoustic stimulation 23 . The majority of the 55 studies aimed at validating CTG waveform assessment methods were published between 1974 and 2023, and the studies included 34 cohort studies, 13 case control studies, six cross sectional study, a before and after study, and a nested case control study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations